2017
DOI: 10.1515/vzoo-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Vertebrates of Post-Quarrying Sites in the Donbas Region of Ukraine

Abstract: Terrestrial Vertebrates of Post-Quarrying Sites in the Donbas Region of Ukraine. Ulyura, E., Tytar, V.-An inventory of terrestrial vertebrates in six post-quarrying sites in the Donbas Region of Ukraine revealed 104 species (2 amphibian, 6 reptile, 78 bird and 18 mammal species). Th e potential of these sites was confi rmed for sustaining and conservation of numerous species of terrestrial vertebrates; some relationships were considered between environmental heterogeneity and species richness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…e closure and/or reduced operations of industrial plants and agricultural processing facilities in the eastern part of Ukraine [Burakovsky & Betliy 2009] seem to have facilitated this trend. Later it was shown that abandoned in the Donbas region quarrying and coal mining sites, with the encroachment of vegetation, notably enhance biodiversty [Ulyura & Tytar 2017, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…e closure and/or reduced operations of industrial plants and agricultural processing facilities in the eastern part of Ukraine [Burakovsky & Betliy 2009] seem to have facilitated this trend. Later it was shown that abandoned in the Donbas region quarrying and coal mining sites, with the encroachment of vegetation, notably enhance biodiversty [Ulyura & Tytar 2017, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The closure and/or reduced operations of industrial plants and agricultural processing facilities in the eastern part of Ukraine (Burakovsky, Betliy, 2009) seem to have facilitated this trend. Later it was shown that abandoned in the Donbas region quarrying and coal mining sites, with the encroachment of vegetation, significantly enhance biodiversty (Ulyura, Tytar, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the analysis of the avifauna is a fairly reliable bioindication method for the restoration of transformed areas that are subject to technogenic impact (Lehikoinen, 2013;Catarino et al, 2016). Given the rather large areas of territories of technogenic origin, in Ukraine (Shapar & Mikheyev, 2018) there is an urgent need to study the features of the formation and patterns of ornithocenoses within such biotopes, as well as develop recommendations for their conservation and management development (Baczyńska et al, 2017;Gavris et al, 2017;Ulyura, 2018).…”
Section: Introductionmentioning
confidence: 99%